Framing of Civil Society Organizations’ Communication on Facebook: Examining the Impact on Audience Engagement in Norway - Enjolras Bernard (Nonprofit Policy Forum)
Public support is crucial for mitigating and adapting to the effects of climate change. Civil Society Organizations (CSOs) play a significant role in normative governance aimed at influencing attitudes and mobilizing citizens to take action. Civil society organizations (CSOs) use digital media to this purpose. The framing of information presented by CSOs has been shown to shape how people perceive and respond to it. This paper aims to examine how cognitive or topical framing and moral foundational framing interact in predicting public engagement with CSOs’ communication about climate change on Facebook. To this end, several computational methods – including topic modeling, semantic network analysis, and automatic text processing based on a Moral Foundations dictionary – are combined, using data gathered on Facebook. The results of the empirical analysis reveal that CSOs use different topical frames and moral foundations in order to influence policymakers and mobilize citizens. CSOs elicit most engagement on Facebook when they combine a “Climate mobilization” topical frame with the moral foundations of care and fairness pertaining to the ethics of autonomy.